Formation Of Local Wisdom About Earth and Space: an Analysis Of Thinking Pattern - Eko Juliyanto; Eli Trisnowati (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Local wisdom has a role in reducing the impact of disasters. However, so far, local wisdom has not been a subject of study in disaster education. Kedu's residence in a disaster-prone area has a wealth of local wisdom that can be used as study material in disaster education. The phenomenon of disaster is related to the phenomena of earth and space so that the local wisdom of the community that can be used as material for study in disaster education is contained in the local wisdom of the community about earth and space phenomena. Therefore, to obtain data on local community wisdom about the disaster, a study of earth and space phenomena is needed. Study material in a scientific discipline must be scientific knowledge. The local wisdom of the community is not a scientific product. For this reason, scientific testing of the local community's livelihoods can be used as material for studies in disaster education. One way to test the knowledge of a knowledge product is to analyze the reasoning pattern of the knowledge product. For this reason, this study aims to analyze the pattern of reasoning to be used as a study material in disaster education and to categorize knowledge in the local wisdom of the ex-Karisidenan Kedu people on Earth and Space as misconceptions or P-Prims. This study uses qualitative research methods with the type of The Investigation of Lived Experience with the type of Cognitive Psychology. The stages of this research are literature study, data collection, and data analysis. Data analysis using the method of fixed comparison with a sequence of work steps as follows: Organizing Data, Data Reduction, Categorization, Synthesis, Compiling